Nb/Ta systematics in arc magma differentiation and the role of arclogites in continent formation - Ming Tang (Nature Portfolio, 2019)
It is unclear why the crust among many arcs is so silica rich when there is a missing mafic component. Here the authors compile a global evaluation of Nb/Ta and examine xenoliths from Arizona to derive a model of why Nb/Ta fractionation is favored in the crust.